Լոռու մարզի ժայռապատկերները - Թոխաթյան, Կարեն (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
Rock art in Armenia originated in the 7th-5th millennia BC. Certain ancient compositions and styles naturally continued in other areas of Armenian culture. The traditions of petroglyphs are observed in bas-reliefs and frescoes of the Early Iron Age and cuneiform periods, as well as in ancient and medieval structures and caves. The skills of carving have been preserved in constructions, sculpture, cuneiform and lapidary inscriptions. Petroglyphs of Lori region and signs on religious buildings located mainly in low mountain areas demonstrate thematic and stylistic, technical and topographical similarities with high-mountain images throughout Armenia, testifying to the continuity of carving traditions among Armenians. The petroglyphs are direct evidence that the Armenian Highland represents a single whole by rock art monuments as well. Thus, the continuity of anthropological and cultural picture is clearly traced in space (400.000 kand in time (hundreds of millennia).
Keywords: Պատմություն; Մշակույթ